2007
DOI: 10.1177/001440290707300201
|View full text |Cite
|
Sign up to set email alerts
|

How Variable are Interstate Prevalence Rates of Learning Disabilities and other Special Education Categories? A Longitudinal Comparison

Abstract: This study compared interstate variability of prevalence rates for special education categories from 1984 to 1985 through 2001 to 2002, using the coefficient of variation (CV), which is designed to compare variances when the means of the groups compared are radically different. The category of learning disabilities, presumed by many to be the most variable, was consistently the least variable. Furthermore, as a group, high incidence categories were less variable than low incidence categories. The results stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 21 publications
(17 reference statements)
3
33
0
Order By: Relevance
“…Results of the current study indicate that the substantial state-level variability in the identification rates of students with ED continues to reflect patterns reported in previous decades (Coutinho & Oswald, 1996;Hallahan et al, 1986;Hallahan et al, 2007). In this case, the range showed that some states identified five times as many students, by percentage, as having ED as did other states.…”
Section: Ed Identification and Educational Environment Placement Ratessupporting
confidence: 61%
See 2 more Smart Citations
“…Results of the current study indicate that the substantial state-level variability in the identification rates of students with ED continues to reflect patterns reported in previous decades (Coutinho & Oswald, 1996;Hallahan et al, 1986;Hallahan et al, 2007). In this case, the range showed that some states identified five times as many students, by percentage, as having ED as did other states.…”
Section: Ed Identification and Educational Environment Placement Ratessupporting
confidence: 61%
“…These data, and their long-term implications, highlight the pertinence of identifying variables associated with the state-level differences in educational outcomes of students with ED. Although difference in graduation rates may be ostensibly related to the differences in educational placement and identification rates previously reported in this and other studies (Coutinho & Oswald, 1996;Hallahan et al, 1986;Hallahan et al, 2007;Landrum et al, 2012), additional examination of this issue is warranted. The following results represent preliminary findings pertaining to this issue.…”
Section: Rates Of Exiting With a Regular Diplomamentioning
confidence: 72%
See 1 more Smart Citation
“…It is easy to think of situations where identifying as many cases from a smaller target group is the most important goal of the analysis. For example, learning disabled students typically make up approximately 3-10% of the overall student population (Hallahan et al, 2007), and thus (when samples are representative of the population) we would see a sample size ratio of likely at most, 10:90. When screening students for learning problems, it is arguably more important to find as many of the at risk students as possible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an individual state's eligibility requirements can change at any time, which can result in changes in the number of classifications within each state from year to year (OSEP 2006a). While much of the controversy and implications regarding the impact of interstate variability in eligibility criteria have focused on the Learning Disability category (e.g., Reschly and Hosp 2004); Hallahan et al (2007) found that such variability did not have a significant impact on the prevalence rate of ''high incidence'' categories. Rather, they conclude that inter-state variability has a more significant impact on ''low incidence'' categories, such as Autism, which accounted for only approximately 4-5% of all special education classifications in 2007 (OSEP 2008).…”
Section: Introductionmentioning
confidence: 99%